2015
DOI: 10.1007/s11250-015-0791-x
|View full text |Cite
|
Sign up to set email alerts
|

Sugarcane and mulberry silage supplementation of sheep during the peripartum period

Abstract: The aim of this study was to evaluate the effects of supplementation with silage made from sugarcane alone or mulberry and sugarcane on the gastrointestinal nematodes and hematological parameters in peripartum Santa Inês ewes. Three groups, each of 15 ewes, were supplemented with either 100 % sugarcane silage or sugarcane silage and mulberry at ratios of either 75:25 or 50:50. The variables analyzed were weight, body condition, packed cell volume, total plasma protein, hemoglobin, total leukocytes, eosinophils… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…In this study, however, these concentrations were also found in resistant ewes, emphasizing the physiological immunity decrease during peripartum. Offering a high-energy and high-protein diet in such period plays a vital role in minimizing infection damage and improving animal performance (42). Dietary supplementation aids replacing nutrients and maintaining the body mass during postpartum of sheep, making them more resistant and apt to cope with this sensitive period (2,43).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, however, these concentrations were also found in resistant ewes, emphasizing the physiological immunity decrease during peripartum. Offering a high-energy and high-protein diet in such period plays a vital role in minimizing infection damage and improving animal performance (42). Dietary supplementation aids replacing nutrients and maintaining the body mass during postpartum of sheep, making them more resistant and apt to cope with this sensitive period (2,43).…”
Section: Discussionmentioning
confidence: 99%
“…When animals' resistance decreases, problems with verminosis are even more pronounced, resulting in a decrease in production and high mortality. 25 The increased susceptibility to gastrointestinal nematodes in sheep in the final third of gestation and lactation (peripartum period), promoted by the peripartum phenomenon, leads to the alteration of some physiological parameters, identified through fecal and blood tests that are performed simultaneously to guarantee more accurate diagnosis of the degree of parasite infection. 4,12 During the experimental period, all sheep had a PCV lower than reference values for the species.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the decrease in total leukocytes and eosinophils in H20, the cause may be related to a greater migration of these defense cells to the site of infection and, consequently, a decrease in their general blood circulation. 25…”
Section: Discussionmentioning
confidence: 99%
“…However, steers fed the SMFP diet had lower ammonia N in the rumen and lower intramuscular fat content [ 123 ]. Multiple studies found that mulberry silage was a cost-effective protein alternative for sheep [ 125 , 126 ] and lambs [ 127 ]. Sun et al [ 128 ] found that partially replacing wildrye hay with mulberry leaves in the diet of sheep, improved the growth performance and carcass characteristics.…”
Section: Application Of Mulberry Tree Extracts In Animal Productionmentioning
confidence: 99%